Effects of glutamine on performance and intestinal mucosa morphometry of broiler chickens vaccinated against coccidiosis - Luquetti, Brenda Carla [UNESP]; Fernandez Alarcon, Miguel Frederico [UNESP]; Lunedo, Raquel [UNESP]; Borges Campos, Daniel Mendes [UNESP]; Furlan, Renato Luis [UNESP]; Macari, Marcos [UNESP] (Univ Sao Paolo, 2016)
This study aimed to assess the effects of glutamine as feed additive on performance and intestinal mucosa morphometry of broiler chickens vaccinated against coccidiosis. A total of 400 day-old male chicks were randomly assigned to four treatments (NVNG - no vaccination, no glutamine supplementation; NVG - no vaccination, glutamine supplementation (10 g kg(-1)); VNG - vaccination, no glutamine supplementation; VG - vaccination, glutamine supplementation) replicated four times with 25 birds per replicate. A commercial sprayed-on vaccine against coccidiosis containing Eimeria acervulina, E. maxima, E. mivati, and E. tenella was administered at the hatchery. Broiler performance was evaluated from 1-28 days, and morphometric parameters were analyzed at 14, 21, and 28 days of age. Body weight gain and feed intake were negatively affected by vaccination, but not by glutamine. Vaccination increased crypt depth in the duodenum and jejunum at 21 and 28 days. In conclusion, this study showed that glutamine was not able to increase weight gain of broiler chickens, irrespective of whether the animals were vaccinated or not against coccidiosis. Glutamine supplementation was able to improve feed conversion in vaccinated birds suggesting trophic effect on intestinal epithelium improving.
Keywords: anticoccidial vaccines; intestinal ephitelium; gut morphometry; glutamine supplementation; small intestine